2021
DOI: 10.1136/bmjgh-2020-002452
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of community health systems strengthening: quality improvement interventions at community level to realise maternal and child health gains in Kenya

Abstract: IntroductionImprovements in maternal and infant health outcomes are policy priorities in Kenya. Achieving these outcomes depends on early identification of pregnancy and quality of primary healthcare. Quality improvement interventions have been shown to contribute to increases in identification, referral and follow-up of pregnant women by community health workers. In this study, we evaluate the cost-effectiveness of using quality improvement at community level to reduce maternal and infant mortality in Kenya.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The community health strategy in Kenya has been shown to be a cost-effective approach for delivering quality maternal and child health services at the household level (Kumar et al ., 2021 ). CHVs are at the center of the community health strategy because they support the uptake of primary health services and, generally, they have built trust and credibility in their communities (WHO and UNICEF, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The community health strategy in Kenya has been shown to be a cost-effective approach for delivering quality maternal and child health services at the household level (Kumar et al ., 2021 ). CHVs are at the center of the community health strategy because they support the uptake of primary health services and, generally, they have built trust and credibility in their communities (WHO and UNICEF, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While resources were limited, QI could also be cost-effective. All six studies evaluating the cost of QI programs in partnerships in LMIC found the QI approach to be cost-effective (23,54,122,(126)(127)(128)(129)(130). One author noted how local NGOs can compete for funding and resources but collaborative QI had the opportunity to bring them together to meaningfully collaborate and learn from each other (35).…”
Section: Theme Iv: Resilience In Managing External Challengesmentioning
confidence: 99%
“…Gartner explained how cyber security risks pervade every organization and are not always under the direct control of an information technology department. Increased cyber risk is real but so are the data security solutions ( Kumar et al, 2021 ). Solutions are costly but effective; for the banking industry, the wealth of numerous customers is at stake, and securing the cost of the system through AI is cost-effective management as less human involvement and training modules are involved.…”
Section: Literature Reviewmentioning
confidence: 99%